2002
DOI: 10.1080/09712119.2002.9706376
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Activates Behavior of Neonatal Chicks in a Short Period of Post-Intracerebroventricular Injection

Abstract: Saito, E., Takagi, T., Nakanishi, T., Sashihara, K. and Furuse, M. 2002. Ghrelin activates behavior of neonatal chicks in a short period of postintracerebroventricular injection. J . Appl. Anim. Res., 22: 33-41. Ghrelin, a novel growth hormone (GH)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The effect was not altered by capsaicin treatment which indicate that peripheral des-acyl ghrelin may induce anorexigenic function by direct activation of brain receptor by crossing the blood-brain barrier but not by the activation of vagal afferent pathways (Chen et al, 2005). Although little is known about des-ghrelin in birds, Saito et al (2002) reported that icv injection of des-ghrelin did not change feed intake in neonatal chicks. However, in the present study, we reported that activity of ghrelin was restricted after peripheral blocking of CRH receptors in 7-day-old chickens.…”
Section: Discussionmentioning
confidence: 93%
“…The effect was not altered by capsaicin treatment which indicate that peripheral des-acyl ghrelin may induce anorexigenic function by direct activation of brain receptor by crossing the blood-brain barrier but not by the activation of vagal afferent pathways (Chen et al, 2005). Although little is known about des-ghrelin in birds, Saito et al (2002) reported that icv injection of des-ghrelin did not change feed intake in neonatal chicks. However, in the present study, we reported that activity of ghrelin was restricted after peripheral blocking of CRH receptors in 7-day-old chickens.…”
Section: Discussionmentioning
confidence: 93%
“…ICV-injected ghrelin induces several behavioral changes such as vocalization and hyper activity in neonatal chicks (Saito et al, 2002b). These behaviors are also induced by ICV injection of corticotropin-releasing hormone (CRH) (Zhang et al, 2001a), and CRH itself is regarded as an anorexigenic peptide in chicks (Furuse et al, 1997b).…”
Section: Peripheral Peptidergic Hormonesmentioning
confidence: 99%
“…Numerous studies with birds have now clearly shown that ghrelin administered icv inhibits food intake in a dose-dependent manner under both fed and fasted conditions [ 2 5 , 17 , 29 , 43 , 44 ]. In contrast, central administration of des-acyl ghrelin had no effect on food intake in neonatal chicks [ 45 ]. However, peripheral administration of ghrelin produced some conflicting findings with respect to its effects on food intake [ 18 , 29 , 46 ].…”
Section: Physiological Actions Of Proghrelin-derived Peptidesmentioning
confidence: 99%
“…As part of the studies of the various physiological actions of ghrelin in birds, it has been noted that this peptide also has important impacts on behavior. For example, ghrelin has been reported to induce sleep-like behavior in a dose-dependent manner when administered centrally to fed or fasted neonatal chicks suggesting that this behavior may be related to its inhibitory effect on food intake [ 45 , 61 ]. However, the sleep-like behavior was preceded by a short period (less than 30 minutes) of hyperactivity and increased vocalization [ 61 ].…”
Section: Physiological Actions Of Proghrelin-derived Peptidesmentioning
confidence: 99%